Implementasi Performance Management System pada Unit Aviation Security di Bandar Udara Internasional Yogyakarta - Walid Jumlad; Ajie Febrianto T (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
To improve the quality of human resources, the role of the Performance Management System (PMS) is very important, as well as a crucial foundation for achieving productivity and sustainable progress of an organization. This study focuses on the Implementation of the Performance Management System in the Aviation Security unit at Yogyakarta International Airport. This study employs a qualitative research method, collecting primary data through interviews and observations, as well as secondary data from documents related to performance assessments and documented events. This study was conducted from August to September 2024 at Yogyakarta International Airport. The data collection techniques used were observation, interviews, and documentation. While the data analysis technique used data collection, data reduction, data presentation, and conclusion. The results of the study show that the implementation of PMS at Aviation Security YIA went through four main stages: Planning (Plan), Action (Act), Monitoring (Monitoring), and Assessment (Review). Planning constraints (adjustment of ambitious targets, personnel understanding) were overcome by involving the Chief and structured socialization. Action steps to deal with decreased motivation, fatigue, and a mentality that already memorizes, which reduces compliance and responsibility, are overcome through continuous training, strengthening leadership, instilling a culture of belonging, and a reward-punishment system. Monitoring is constrained by personal assessment, manual observation, large data volumes, and a limited number of Chiefs, overcome with objective training, standardization of checklists, and optimization of CCTV. Assessment and feedback face potential bias and personnel disagreement, overcome with counseling, training, mentoring, and disciplinary action.